2011
DOI: 10.1371/journal.pone.0018376
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of Kallikrein 6 in Regulating Immune Cell Survival

Abstract: BackgroundKallikrein 6 (KLK6) is a newly identified member of the kallikrein family of secreted serine proteases that prior studies indicate is elevated at sites of central nervous system (CNS) inflammation and which shows regulated expression with T cell activation. Notably, KLK6 is also elevated in the serum of multiple sclerosis (MS) patients however its potential roles in immune function are unknown. Herein we specifically examine whether KLK6 alters immune cell survival and the possible mechanism by which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 63 publications
3
48
0
1
Order By: Relevance
“…(The relatively high pcercentage of dead cells in the spleen is normal because it is the center for removal of old and exhausted immune cells. 37 ) A final set of studies focused on assessment of the cytotoxicity of dissolved and extractable components from the solution. Here, extracts consisted of a culture medium used to Figure S8a in the SI shows phase-contrast microscope images of cells treated with 100% extract for 72 h. No significant morphological signs of damage appear for extracts from poly-Si, a-Si, SiGe, Ge, or mono-Si, similar to negative control samples (HDPE).…”
Section: Resultsmentioning
confidence: 99%
“…(The relatively high pcercentage of dead cells in the spleen is normal because it is the center for removal of old and exhausted immune cells. 37 ) A final set of studies focused on assessment of the cytotoxicity of dissolved and extractable components from the solution. Here, extracts consisted of a culture medium used to Figure S8a in the SI shows phase-contrast microscope images of cells treated with 100% extract for 72 h. No significant morphological signs of damage appear for extracts from poly-Si, a-Si, SiGe, Ge, or mono-Si, similar to negative control samples (HDPE).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro, Klk6 promotes inflammatory cell survival [41] and clinical studies show that KLK6 is elevated in patients with inflammatory demyelinating conditions [42]. These data are particularly relevant because TBI-associated symptoms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of these proteins lead to increased permeability of the BBB and free inflammatory cells to migrate to injury sites leading to increased demyelination and neuronal cell death. As macrophages migrate to aid in remodelling damaged central nervous system (CNS) tissue, they secrete Klk6 [41]. Increasing abundance of such inflammatory cells compounds the breakdown of ECM proteins as pro-inflammatory molecules are secreted, which allows for expansion of the inflammation and cell death beyond the immediate area of impact and escape of the molecules into systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Signalling via this PAR and PAR2 induced by both KLK2 and KLK4 enhanced proliferation of prostate cancer DU145 cells (Mize et al, 2008). Interestingly, using murine whole splenocyte preparations and the human Jurkat T cell line it has been shown that KLK6 via PAR1 promotes pro-survival and inhibits pro-apoptotic mechanisms, leading to vigorous splenic T cell survival in the presence of the cell death inducing agents, camptothecin, dexamethasone, staurosporine and Fas-ligand (Scarisbrick et al, 2011). This KLK can also initiate intracellular signalling in neurons via PAR1 and in astrocytes through both PAR1 and PAR2 (Vandell et al, 2008) and has recently been reported to serve as a molecular trigger via PAR1 of processes involved in development of astrogliosis (Scarisbrick et al, 2012a).…”
Section: Klk1mentioning
confidence: 99%